Effects of low-dose warfarin and regional chemotherapy on survival in patients with pancreatic carcinoma - Nakchbandi, Wes; Müller, Herwart; Singer, Manfred V.; Löhr, J.-Matthias; Nakchbandi, Inaam (Scandinavian journal of gastroenterology, 2006)
OBJECTIVE: To report the effect of regional combination chemotherapy in a cohort of patients with inoperable pancreatic carcinoma treated with or without low-dose warfarin. MATERIAL AND METHODS: A retrospective analysis was performed on 180 patients with pancreatic carcinoma. Patients received one of seven regimens of chemotherapy. Unrelated to the type of chemotherapy, some patients received 1.25 mg warfarin daily. The primary end-point was median survival. RESULTS: Treatment with warfarin resulted in improved median survival from the start of regional therapy (warfarin versus no warfarin: 5.0 versus 2.3 months, n = 111 versus 69; p < 0.0001). This effect was not dependent on the type of chemotherapy used. Among the seven regimens examined, the one consisting of regional gemcitabine and mitomycin-C with systemic gemcitabine was associated with the longest median survival of 5.1 months from the start of regional therapy (p = 0.006) and 12.7 months from diagnosis. This regimen combined with warfarin was associated with improved median survival (7.1 months, n = 32). CONCLUSIONS: Treatment with low-dose warfarin improved survival irrespective of the chemotherapy received. Of the regimens examined, the combination of regional gemcitabine and mitomycin-C with systemic gemcitabine was associated with the longest survival time. Survival was increased further by the addition of warfarin. These data provide a rationale, based on safety and efficacy, for a definitive study on the use of warfarin and combined regional and systemic chemotherapy in patients with pancreatic carcinoma.
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 30.06.2021